Panzer Battles : A Study of the Employment of Armor in the Second World War - Mellenthin, F. W. Von, (Maj. Gen.) 1904-1997; Translated by H. Betzler, Edited by L. C. F. Turner (Rawalpindi, Pakistan Army Education Publishing House, 2003)
Armored warfare assumed vital importance in World War II, and during the first years of the war despite inferiority in numbers and equipment, the German Army was master. The secret of Germany's early successes and the reason for its eventual failure are disclosed in this analysis by a brilliant former general of the German Army. Major General von Mellenthin, who saw action in every theater of the European war from 1939 to 1945, follows the panzer armies through Poland, France, the Balkans, across the deserts of North Africa and the frozen wastes of Russia, to the final defeat on the Western front. It was the decisive victories of the German panzer divisions in North Africa that taught the Allies the importance of an integrated combat team consisting of tanks, infantry and artillery.
Include Colour Illustration, Map, Appendix and Index
Keywords: World War (1939-1945) -- Military campaigns -- Tank warfare